THE BASIC PRINCIPLES AND RULES OF PROVIDING AND SUPPORT OF CIVIL UNMANNED AVIATION SYSTEMS PERFORMANCE - Тамаргазін, О.; Ліннік, І. (Science-based technologies, 2012)
The questions of building a system to ensure the airworthiness of unmanned aircraft systems for use in various industries. Formulated the most important requirements for the composition and content of the basic concepts of the security of airworthiness. Analyzed the main international standards, which should be the basis established in Ukraine normative documents to regulate the use of unmanned aerial vehicles are not in military operations.